Trends in Land Use, Irrigation, and Streamflow Alteration in the Mississippi River Alluvial Plain - Yasarer, Lindsey M. W.; Taylor, Jason M.; Rigby, James R.; Locke, Martin A. (Frontiers in Environmental Science, 2020)
The Mississippi River Alluvial Plain is a critical region for agricultural production in the United States, providing the majority of the nation’s rice, catfish, and cotton. Although it is a humid region, high agricultural yields are maintained through irrigation from groundwater and surface water sources. Heavy groundwater extraction has led to cones of depression in the alluvial aquifer in both Arkansas and Mississippi. This study explores the link between increasing irrigation and streamflow alteration within the alluvial plain. Changing land use patterns were evaluated utilizing the USDA Census of Agriculture datasets to determine changes in land-use, irrigation, and crop yield from 1969 to 2017. Temporal land use patterns set the background for the analysis of sixteen long-term streamflow records from the USGS, which were assessed using the Indicators of Hydrologic Alteration (IHA) software to determine changes in low flow patterns in rivers overlying the Mississippi River Valley alluvial aquifer. Most streamflow records had significant hydrologic alteration with respect to low flow conditions, including higher frequency of low flow events, lower annual minima, or a declining base flow index. Changes in streamflow coincide with areas of massive increases in irrigated cropland area. This study provides further context for the tradeoffs between intensive agricultural production and agroecosystem sustainability.